2014
DOI: 10.3233/jad-140315
|View full text |Cite
|
Sign up to set email alerts
|

Active Invasion of Porphyromonas gingivalis and Infection-Induced Complement Activation in ApoE-/- Mice Brains

Abstract: Periodontal disease is a polymicrobial inflammatory disease that leads to chronic systemic inflammation and direct infiltration of bacteria/bacterial components, which may contribute to the development of Alzheimer's disease. ApoE-/- mice were orally infected (n = 12) with Porphyromonas gingivalis, Treponema denticola, Tannerella forsythia, and Fusobacterium nucleatum as mono- and polymicrobial infections. ApoE-/- mice were sacrificed following 12 and 24 weeks of chronic infection. Bacterial genomic DNA was is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
179
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 65 publications
7
179
1
5
Order By: Relevance
“…All are potential causes for the development of sporadic AD. P. gingivalis was shown to migrate from its oral location to the brain [54,55] where it invoked inflammatory responses typical of neurodegenerative diseases in mice with blood–brain barrier (BBB) damage [55,56]. Ishigami et al [57] identified glial fibrillary acidic protein (GFAP), a marker of astrocytes in the AD brain, to be a substrate for host PAD2, and suggested a role for the citrullinated GFAP in the progression of this neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…All are potential causes for the development of sporadic AD. P. gingivalis was shown to migrate from its oral location to the brain [54,55] where it invoked inflammatory responses typical of neurodegenerative diseases in mice with blood–brain barrier (BBB) damage [55,56]. Ishigami et al [57] identified glial fibrillary acidic protein (GFAP), a marker of astrocytes in the AD brain, to be a substrate for host PAD2, and suggested a role for the citrullinated GFAP in the progression of this neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
“…Once in the brain, P. gingivalis modulates innate immune responses via activation of the complement cascade, resulting in bystander injury of functional pyramidal neurons in the hippocampus, following 24 week of chronic infection [34]. A recent investigation using the same ApoE -/-P.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported associations between P. gingivalis LPS and AD brains [33] and subsequently established that P. gingivalis is capable of accessing ApoE -/-mouse brains from its primary gingival location [32,34]. Once in the brain, P. gingivalis modulates innate immune responses via activation of the complement cascade, resulting in bystander injury of functional pyramidal neurons in the hippocampus, following 24 week of chronic infection [34].…”
Section: Introductionmentioning
confidence: 99%
“…The downstream effects of P. gingivalis mono-infection in ApoE -/-mice was recently reported by Poole et al [132] in which they reported the translocation of this PD pathogen from the oral cavity into the brain tissue likely via the haematogenous route; although other pathways for its translocation are also possible [133].…”
Section: Experimental Periodontitis In Apoe −/− Mice Initiate Inflammmentioning
confidence: 99%
“…Examination of the brain tissue highlighted the brains own inflammatory cells (microglia and astrocytes) were activated and neurons were being attacked by excessive complement activation supporting ongoing intracerebral inflammation in the absence of AD hallmark proteins [132]. For the relevance of finding P.…”
Section: Experimental Periodontitis In Apoe −/− Mice Initiate Inflammmentioning
confidence: 99%